Analysis of the characteristic lengths in the bubble and slug flow regimes generated in a capillary T-junction. (December 2016) - Arias, S.; González-Cinca, R.
Highlights: Experimental setup provides regular trains of bubbles with small size dispersion. The volume of liquid to generate a bubble is constant in the saturation regime. Bubble volume is proportional to the ratio of gas–liquid superficial velocities. New predictions for the unit cell and the bubble characteristic lengths. Predictions for the bubble length in the bubble and the slug flow regimes. Abstract: We present an analysis of the geometry of the continuous and disperse phases in the bubble and slug flow regimes in air–water mixtures generated in a capillary T -junction of 1  mm internal diameter. Bubble size dispersion is very low in the considered flow patterns. The concept of unit cell is used to identify two characteristic lengths of the two-phase flow, namely, the unit cell length and the bubble length. The relationship between these lengths and the gas and liquid superficial velocities, gas mean velocity, bubble generation frequency and volume average void fraction is analysed. We conclude that in the considered configuration the unit cell and bubble lengths can be predicted either by the ratio of the gas–liquid superficial velocities or the volume average void fraction.